Atrial septal defect patients have an elevated risk for infective endocarditis - Muroke Valtteri; Jalanko Mikko; Haukka Jari; Pätilä Tommi; Hartikainen Juha; Tahvanainen Anna; Ukkonen Heikki; Ylitalo Kari; Anttila Vesa; Pihkala Jaana; Sinisalo Juha (TAYLOR & FRANCIS LTD, 2025)
Background. It has been unclear whether simple atrial septal defect (ASD) is an independent risk factor for infective endocarditis (IE). This study aimed to untangle the risk of endocarditis in a large nationwide cohort.
Methods. We acquired data from the Finnish hospital discharge register on all individuals with ASD diagnosis from 1969 to 2019. Patients with complex congenital cardiac abnormalities were ruled out. Five individualized controls from the general population were matched to the ASD patient's birth year, sex, and residence at the index date. All the patients with ICD-8, -9, or -10 diagnosis codes for IE were gathered from the hospital discharge registry.
Results. Altogether, 8322 patients with ASD and 39,237 individualized controls were enrolled in the study. Median follow-up was 21.6 years (IQR 11.8-36.9) from the first hospital contact. In total, 24 (16 male) cases of infective endocarditis among ASD patients and 10 (8 male) cases among controls were diagnosed during the follow-up. The incidence of endocarditis was 0.11 per 1000 person-years in the patients with ASD and 0.011 per 1000 person-years in the controls. The adjusted risk ratio for endocarditis was 13.51 (95% CI: 6.20-29.46) in patients with ASD compared to the control cohort. Patients with ASD and endocarditis had higher long-term mortality than individualized control patients (MRR 2.25, 95% CI: 1.23-4.11).
Conclusions. The incidence of IE in patients with ASD was higher than in the general population. Mortality associated with IE was higher in patients with ASD compared to controls.